2014
DOI: 10.1007/s00284-014-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Probiotic Strains of Lactobacillus on In Vitro Adherence of Listeria monocytogenes, Streptococcus agalactiae, and Staphylococcus aureus to Vaginal Epithelial Cells

Abstract: The lactobacilli probiotics maintain a normal vaginal biota and prevent disease recurrence. This microorganisms form a pellicle on the vaginal epithelium that acts as a biologic barrier against colonization by pathogenic bacteria. In this paper were realized assays of exclusion, competition, and displacement. For these test, vaginal epithelial cells, two strains of lactobacilli and pathogenic bacteria (Staphylococcus aureus, Streptococcus agalactiae and Listeria monocytogenes) were used. The lactobacilli strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 18 publications
1
17
0
7
Order By: Relevance
“…Interestingly, an inverse relationship between Lactobacillus and GBS has also been observed in cows with subclinical mastitis ( 79 ). Certain Lactobacillus strains have the capacity to inhibit GBS adherence to vaginal epithelial cells ( 80 , 81 ), and antimicrobial activity of Lactobacillus against GBS has been documented in vitro ( 82 ) and reduction of colonization seen in vivo ( 83 , 84 ). Although the full complexity of the vaginal microbiome is only now being characterized, preliminary in vitro studies have begun to probe GBS communication and cooperation with other microbes in this host microenvironment.…”
Section: Influence Of Vaginal Microbiota On Gbs Colonizationmentioning
confidence: 99%
“…Interestingly, an inverse relationship between Lactobacillus and GBS has also been observed in cows with subclinical mastitis ( 79 ). Certain Lactobacillus strains have the capacity to inhibit GBS adherence to vaginal epithelial cells ( 80 , 81 ), and antimicrobial activity of Lactobacillus against GBS has been documented in vitro ( 82 ) and reduction of colonization seen in vivo ( 83 , 84 ). Although the full complexity of the vaginal microbiome is only now being characterized, preliminary in vitro studies have begun to probe GBS communication and cooperation with other microbes in this host microenvironment.…”
Section: Influence Of Vaginal Microbiota On Gbs Colonizationmentioning
confidence: 99%
“…Our study revealed that colonization of A. baumannii in the presence of either GBS and/or C. albicans did not increase the possibility of PPROM. We postulate that vaginal microbiota, especially Lactobacilli, may outcompete the adherence of GBS and other pathogens to the vaginal epithelial cells as previously demonstrated by Ortiz et al (2014) and Parolin et al (2015). Apart from that, epithelial cells of the vagina were also reported to produce antimicrobial compounds (Yarbrough et al, 2015).…”
Section: Discussionmentioning
confidence: 53%
“…These interactions vary between the microorganisms: cooperation with E. faecalis and Candida albicans (Engelmann et al, 2011; Nair et al, 2014; Zago et al, 2015), competition with Lactobacillus sp. (Ortiz et al, 2014), and Streptococcus pneumoniae (Margolis et al, 2010). S. aureus can also have both interactions (competition and cooperation) with the same pathogen depending of the disease and the conditions such as Pseudomonas aeruginosa (Hoffman et al, 2006; Baldan et al, 2014; Serra et al, 2015; Frydenlund Michelsen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%